PENGARUH ETOS KERJA, BUDAYA ORGANISASI DAN KOMITMEN KARYAWAN TERHADAP KINERJA KARYAWAN PADA PUSAT PENELITIAN KELAPA SAWIT (PPKS) UNIT MARIHAT PEMATANG SIANTAR - Sitio, Febri Liana; Purba, Betniar; Sitompul, Pandapotan (LPPM Universitas Katolik Santo Thomas Medan, 2024)
This study aims to determine and explain the effect of work ethic, organizational culture and employee commitment on employee performance at the Palm Oil Research Center (PPKS) Marihat Unit Pematang Siantar. The population in this study were 230 permanent employees and the number of samples through the slovin formula with a total of 70 permanent employees. The analysis techniques used in this study are validity and reliability tests, multiple linear regression, t test, F test and the coefficient of determination (R2) using the help of SPSS Version 25. The results showed that there was an influence between the independent variables, namely work ethic, organizational culture and employee commitment on the dependent variable, namely employee performance. From the results of simultaneous testing (F test) shown in the Fcount value of (90,680) > Ftable (2.51) it can be concluded that work ethic, organizational culture and employee commitment have a simultaneous and significant effect on employee performance. From the results of partial testing (t test) obtained the value of Work Ethic tcount (6,951) > t table (1,668), Organizational Culture tcount value (4,761) > t table (1,668) and Employee Commitment tcount value (5,359) > t table (1,668). This means that Work Ethic, Organizational Culture and Employee Commitment have a positive and significant effect on Employee Performance at the Palm Oil Research Center (PPKS) Marihat Unit Pematang Siantar. The coefficient of determination (R Square) is 0.805. This means that variations in Employee Performance can be explained by variations in Work Ethic, Organizational Culture and Employee Commitment by 80.5% while 19.5% can be explained by other factors not discussed in this study.